2018
DOI: 10.1038/s41467-018-06575-6
|View full text |Cite
|
Sign up to set email alerts
|

Nickel nanoparticles set a new record of strength

Abstract: Material objects with micrometer or nanometer dimensions can exhibit much higher strength than macroscopic objects, but this strength rarely approaches the maximum theoretical strength of the material. Here, we demonstrate that faceted single-crystalline nickel (Ni) nanoparticles exhibit an ultrahigh compressive strength (up to 34 GPa) unprecedented for metallic materials. This strength matches the available estimates of Ni theoretical strength. Three factors are responsible for this record-high strength: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 50 publications
6
83
1
Order By: Relevance
“…This study emphasizes a particular increase of the yield strength for rounded systems due to a decrease of the contact surface area, and a transition towards a homogeneous dislocation nucleation process for a given range of sample sizes and roundness. Both results were confirmed by Sharma and collaborators [15], in the case of faceted Ni NPs using SEM compression tests and MD. In the latter case, the authors also underline the crucial role of the thin surface oxide layer (observed in the experiments) on the elevated strengths of the NPs.…”
Section: Introductionsupporting
confidence: 62%
“…This study emphasizes a particular increase of the yield strength for rounded systems due to a decrease of the contact surface area, and a transition towards a homogeneous dislocation nucleation process for a given range of sample sizes and roundness. Both results were confirmed by Sharma and collaborators [15], in the case of faceted Ni NPs using SEM compression tests and MD. In the latter case, the authors also underline the crucial role of the thin surface oxide layer (observed in the experiments) on the elevated strengths of the NPs.…”
Section: Introductionsupporting
confidence: 62%
“…It is also noted that kitchen kettles may release nickel into drinking water when it is boiled in kettles with nickel-plated elements. Finally, nickel nanoparticles (NiNPs) are among the most widely used nanomaterials, which are employed in many fields, such as catalysts, magnetic materials, biological medicines, conductive pastes and additive to lubricant [31][32][33].…”
Section: Chemical Form Properties and Sources Of Nickel Compoundsmentioning
confidence: 99%
“…Numerous molecular dynamics simulations of Ni nanoparticles are conducted using embedded atom method parametrization for interatomic potential that reproduces reasonably well the properties of Ni clusters. However, it should be noted, that such studies were devoted to single metal nanoparticles interacting with each other or different metal NP to study the interaction kinetics, melting process, to name a few (Henz et al 2009;Sharma et al 2018;Yousefia and Khoie 2015;Joshi et al 2010). Even though application of Morse potential is the simplification of the real systems, it can provide results of physical relevance.…”
Section: Potential Functionmentioning
confidence: 99%